STEM stereotypes predict students' STEM career interest via self-efficacy and outcome expectations - Tian Luo; Winnie Wing Mui So; Zhi Hong Wan; Wai Chin Li (SpringerOpen, 2021)
Abstract Background Nurturing students' interest in science, technology, engineering, and mathematics (STEM) careers is a major goal of STEM education. Although the relationship between students' stereotypical beliefs regarding STEM careers and their career interest can be reasonably hypothesized, research investigating the extent to which and how students' STEM career interest is directly or indirectly influenced by their stereotypical beliefs is lacking. This study investigated how upper primary students' stereotypical beliefs regarding STEM careers predicted their STEM self-efficacy and STEM career-related outcome expectations and how these constructs predicted their STEM career interest. Structural equation modelling was used to analyse quantitative survey data of 824 fourth- to sixth-grade students and test the hypothesized models. Results Students' stereotypical beliefs regarding STEM careers negatively predicted their self-efficacy in STEM activities and career-related outcome expectations. Additionally, the students' self-efficacy in STEM activities and career-related outcome expectations in turn predicted their STEM career interest. Conclusions These results explain the potential indirect effect of STEM stereotypes on students' career interest through self-efficacy and outcome expectations. The findings highlight the significant role of STEM stereotypes, self-efficacy in STEM activities, and career-related outcome expectations in students' career development. The implications of this study for STEM education are also discussed.